Fungal dilated cardiomyopathy in a child with acute lymphoblastic leukemia, what is the optimal agent and duration in therapy?: A case report - Aylin Canbolat Ayhan; Yusuf Izzet Ayhan; Cetin Timur; Muferet Erguven (Mediterranean Journal of Hematology and Infectious Diseases)
Invasive fungal infection (IFI) is still one of the life-threatening complications seen in patients with prolonged immunosuppressive therapy despite new antifungal agents. Patients diagnosed with leukemia and undergoing remission induction therapy are considered at high risk for IFI. The diagnosis of fungal infection is usually difficult and frequently late. Candida species are uncommon causes of infective myocarditis, endocarditis and dilated cardiomyopathy. Initiation time of antifungal treatment in these patients effects mortality rates. The optimal antifungal choice and duration of treatment of cardiac Candida infections is not well defined yet. Herein, we describe as a rare case of dilated cardiomyopathy, myocarditis and endocarditis due to Candida albicans which was treated successfully with combination of new antifungal agents, caspofungin and voriconazole, in a 4-year-old child diagnosed with acute lymphoblastic leukemia. This case suggests once more that early initiation of antifungal treatment has a profound impact on survival.